Valproic acid's effects on visual acuity in retinitis pigmentosa: a systemic review and Meta-analysis - Chen, Wen-Jun (Int J Ophthalmol, 2019)
AIM: To gain a better understanding of the overall efficacy of valproic acid (VPA) treatment for retinitis pigmentosa (RP). METHODS: Publications in PubMed, EMBASE, Cochrane Library, Web of Science and Clinicaltrials.gov were searched for clinical trials of patients with RP assigned to treatment with VPA. Patients' pre- and post-treatment visual field (VF) and best-corrected visual acuity (BCVA) scores were extracted and compared to assess changes. RESULTS: A total of 78 reports were retrieved and 6 studies involving 116 patients were included in the Meta-analysis. The combined results showed a significant decrease in logarithm of minimal angle of resolution (logMAR) scores, calculated using baseline and post-treatment BCVA (P<0.00001, mean difference=-0.05, 95%CI: -0.05, -0.04, I(2)=36%) scores, which means there was considerable improvement in visual acuity. Meanwhile, more BCVA changes were observed in short-term (≤6mo) treatment studies (P<0.00001, mean difference=-0.05, 95%CI: -0.05, -0.04, I(2)=38%), studies conducted in Asia (P<0.00001, mean difference=-0.05, 95%CI: -0.05, -0.04, I(2)=4%), studies with a sample size of 30 or fewer patients (P<0.00001, mean difference=-0.05, 95%CI: -0.05, -0.04, I(2)=38%) and prospective studies (P<0.00001, mean difference=-0.05, 95%CI: -0.05, -0.04, I(2)=0%). However, VPA's effect on VF was inconsistent across studies (P=0.75, mean difference=-22.76, 95%CI: -160.56, 115.05, I(2)=68%). CONCLUSION: This Meta-analysis reveals that most RP patients who were treated with VPA showed improvement in BCVA. However, its effect on VF remains inconsistent. VPA may be a promising treatment for RP.